Age‐related cataract and 10‐year mortality: the Liwan Eye Study. Issue 3 (27th September 2019) - Zhu, Zhuoting; Wang, Lanhua; Scheetz, Jane; He, Mingguang
Abstract: Purpose: To explore the association between age‐related cataract and 10‐year mortality in an adult population in urban China. Methods: A total of 1405 participants aged 50 years or older were examined at baseline in the Guangzhou Liwan Eye Study. All participants were invited to attend a 10‐year follow‐up visit. Cataract cases were defined as either having visible lens opacity confirmed with direct ophthalmoscope under pupil dilation or previous history of cataract surgery. Visual impairment (VI) was defined as a visual acuity of 20/40 or worse in the better‐seeing eye with habitual correction if worn. Body mass index (BMI) was based on anthropometric data. A brief questionnaire regarding family income, educational attainment and medical history of systemic disease was administered. Mortality rates were compared using the log‐rank test and Cox proportional hazards regression models. Results: Among 1405 participants examined at baseline, 957 participants (68.1%) had visible lens opacity or history of cataract surgery. After 10 years, 320 (22.8%) participants died. The 10‐year mortality rate was significantly higher in participants with cataract than in those without (30.1% versus 7.14%, log‐rank p < 0.05). After adjusting for age, gender, family income, educational attainment, BMI, history of diabetes and hypertension and presence of VI, presence of cataract predicted a nearly threefold increase in the risk of mortality (HR, 2.99; 95% CI, 1.89–4.71). Conclusions: Our findings that age‐related cataract is a predictor for poorer survival compared to those without may imply that cataract is a biomarker of ageing and frailty.